Death and the Civil War [videorecording (DVD)] - Burns, Ric; Burns, Ric; Burns, Ric; Platt, Oliver; Cromwell, James; David, Keith; Hamilton, Josh; Leonard, Robert Sean, 1969-; Madigan, Amy; Marvel, Elizabeth; Faust, Drew Gilpin (PBS Distribution, 2012)
Based on the best-selling book by Drew Gilpin Faust, this film will explore how the American Civil War created a 'republic of suffering' and will chart the far-reaching social, political, and social changes brought about by the pervasive presence and fear of death during the Civil War.